1986
DOI: 10.1212/wnl.36.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Kearns‐Sayre syndrome with coenzyme Q 10

Abstract: We studied the metabolism of coenzyme Q10 (CoQ) and the effects of CoQ therapy in five patients with Kearns-Sayre syndrome (KSS). Although the mitochondrial fraction was increased in muscles from KSS patients, CoQ content was slightly low. CoQ synthesis was normal in fibroblasts from KSS patients. Administration of 120 to 150 mg/d of CoQ improved abnormal metabolism of pyruvate and NADH oxidation in skeletal muscle. CoQ therapy decreased CSF protein concentration and CSF lactate/pyruvate ratio. ECG abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(56 citation statements)
references
References 0 publications
2
51
1
2
Order By: Relevance
“…In several other studies subjects were stressed according to a protocol different from the one applied in the present investigation. 6,10,12,13,[16][17][18][19][20] Generally, a disadvantage of protocols which require an absolute workload is that differences in muscle mass and physical conditioning are not considered, although it is well-known that the lactate increase under a fixed workload may be due to deconditioning and reduced body mass. 17,21 Although a workload relative to the maximal is assumed to give a higher sensitivity and specificity, particularly if the maximal workload is reached stepwise, results of a recent investigation show that cycling with 30% of the maximal workload does not increase the diagnostic yield of the LST.…”
Section: Discussionmentioning
confidence: 99%
“…In several other studies subjects were stressed according to a protocol different from the one applied in the present investigation. 6,10,12,13,[16][17][18][19][20] Generally, a disadvantage of protocols which require an absolute workload is that differences in muscle mass and physical conditioning are not considered, although it is well-known that the lactate increase under a fixed workload may be due to deconditioning and reduced body mass. 17,21 Although a workload relative to the maximal is assumed to give a higher sensitivity and specificity, particularly if the maximal workload is reached stepwise, results of a recent investigation show that cycling with 30% of the maximal workload does not increase the diagnostic yield of the LST.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of coenzyme Q 10 are usually normal in primary muscle coenzyme Q 10 deficiency. Secondary coenzyme Q 10 deficiency in muscle was first reported along with a treatment response in 1986 in Kearns-Sayre syndrome [91]. Since then evidence has accumulated in several studies that a subset of mitochondrial disease patients have muscle coenzyme Q 10 deficiency [92].…”
Section: Skeletal Muscle Analysismentioning
confidence: 99%
“…51 Coenzyme Q 10 therapy was also reported to correct pancreatic b-cell dysfunction in patients with mitochondrial encephalomyopathy and lactic acidosis and diabetes mellitus. 52 However, the most consistent finding appears to be at the biochemical level with a decrease in plasma/serum lactate and pyruvate levels being widely reported following exercise 48,51,53,54,55,56,57,58 . In contrast, some studies have shown no evidence of clinical or biochemical improvement in patients following CoQ 10 supplementation 59,60 .…”
Section: Treatment Of Mrc Disordersmentioning
confidence: 94%